Finite‐time disturbance observer‐based modified super‐twisting algorithm for systems with mismatched disturbances: Application to fixed‐wing UAVs under wind disturbances. (7th July 2021) - Nguyen, Ngo Phong; Oh, Hyondong; Kim, Yoonsoo; Moon, Jun; Yang, Jun; Chen, Wen‐Hua
Abstract: This article proposes a finite‐time disturbance observer‐based modified super‐twisting algorithm (FDO‐STA) for disturbed high‐order integrator‐chain systems under matched and mismatched disturbances. We first design a finite‐time observer for disturbance estimation, in which we show the finite‐time convergence of disturbance estimation errors to zero. Second, by employing the estimates of disturbances and their derivatives, a new dynamic sliding surface is derived, which ensures the finite‐time convergence of the controlled output to zero in the sliding phase. Then, based on the estimates of disturbances and their derivatives, the designed sliding surface, and a modified super‐twisting algorithm, we develop the FDO‐STA, which guarantees the finite‐time convergence of the sliding variable to zero in the reaching phase. Rigorous analysis is provided to show the finite‐time stability of the overall closed‐loop system under the proposed control scheme. We finally apply the proposed FDO‐STA framework to the path following control for fixed‐wing UAVs under wind disturbances. Various simulation results are provided to show the effectiveness of the proposed controller, compared with the existing control approaches.